Career Construction Counseling to Increase Career Adaptability of Undergraduate Students - Yohanes Yohanes; Mungin Eddy Wibowo; Edy Purwanto; Sunawan Sunawan (Universitas Negeri Semarang, 2022)
Abstract. The rapidly changing world of work as the result of globalization in the industrial era 4.0 causes college graduates to feel anxious, insecure, and filled with feelings of uncertainty in determining career choices. Jobs are not guaranteed availability. There is now, tomorrow is gone, so it is difficult to predict whether today's jobs will be secure in the future. The era of disruption makes it difficult for individuals to control their own career destiny. Students need information and a comprehensive picture of themselves and the world of work they will be living in so that they are able to make the right career decisions. The career construction counseling model is considered a career counseling model that is very appropriate in dealing with the world of work in the 21st century or the disruption era. The purpose of this study is to explain how the effectiveness of career counseling career construction counseling model can help students to increase career adaptability so that they can immediately get the desired job after graduation, graduating on time, and be able to adapt in various changes that occur in the world of work when they have worked. This research uses literature studies research method. In this research data collection is carried out by studying and analyzing international journals and books that are considered relevant to the research. The results showed that career construction counseling effective in increasing career adaptability as well as to reduce anxiety, doubt, and uncertainty in career choice.